Du travail et de ses conflits vus du Sud. Pour une étude du champ syndical latino-américain - Franck Gaudichaud (Nuevo mundo - Mundos Nuevos, 2020)
The present work examines the case of a country, Chile, which often considered as a "laboratory of neo-liberalism". It centers round a recent experiment in union revitalisation, namely the creation and development of the "Chilean Harbours Union". I seek to trace the slow incubation of an exceptional trade union experiment in Chilean harbours. The ambition of this work is to bring to light the establishment and deployment, as well as the strengths and weaknesses, of a major trade union, that of the dockers, constrained by the authoritarian legal framework of an "advanced" neo-liberal context in which very precarious working conditions prevail. Beyond the Chilean case, the essay partakes of a wider debate on the origins of workers' resistance in countries of the global South, while also proposing a reflection on the dynamics of union regeneration and politicisation of work and workers.